Global trends to reduce carbon footprint: challenges and opportunities for the Costa Rican health sector - Murillo-Rodríguez , Ericka (2024)
Introduction: The reduction of carbon footprints across all sectors is a crucial aspect of climate action. The implementation of specific strategies to achieve this goal includes the actions of healthcare services. Costa Rica has been noted for a robust health system with a primary care approach. However, there is a paucity of scientific evidence regarding the roles and impacts of the health sector in reducing the national carbon footprint. Objective: To analyze the scientific production on carbon footprint in health services at a global level and contrast it with the Costa Rican reality. Method: A mapping of the literature in Spanish and English was carried out in the Scopus database, based on online thesaurus terms. Inclusion and exclusion criteria were applied, and the Bibliometrix tool in R software was used for the analysis. Subsequently, an integrative review of the selected documents was conducted with the support of the Covidence platform. A total of 46 publications were analyzed in the bibliographic analysis and 25 documents in the scoping review, identifying currently researched topics for carbon footprint reduction in healthcare. These topics include hospital input analysis, solid waste management, environmental impact assessment techniques, sustainability strategy design, environmental education, healthcare infrastructure, sustainable purchasing, and energy consumption. Conclusions: The studies, regardless of region or country, present options for improving healthcare practice in relation to the carbon footprint, also impacting the health of the populations. However, the majority of these studies, according to the GRADE methodology, present low evidence due to the particularities of the methodological design employed. International collaborations can be a useful tool to advance the implementation of technologies and political strategies that are adaptable to the Costa Rican reality, thereby making the health sector and, consequently, healthcare sustainable.